Role of AMP‐Activated Protein Kinase Activators in Antiproliferative Multi‐Drug Pituitary Tumour Therapies: Effects of Combined Treatments with Compounds Affecting the mTOR‐p70S6 Kinase Axis in Cultured Pituitary Tumour Cells. (January 2015) - Tulipano, G.; Faggi, L.; Cacciamali, A.; Spinello, M.; Cocchi, D.; Giustina, A.
<x xml:space="preserve">Abstract</x> AMP‐activated protein kinase (AMPK) is activated under conditions that deplete cellular ATP levels and elevate AMP levels. We have recently shown that AMPK can represent a valid target for improving the medical treatment of growth hormone (GH)‐secreting pituitary adenomas and the effects of its activation or inhibition in pituitary tumour cells are worthy of further characterisation. We aimed to determine whether AMPK may have a role in combined antiproliferative therapies based on multiple drugs targeting cell anabolic functions at different levels in pituitary tumour cells to overcome the risk of cell growth escape phenomena. Accordingly, we tried to determine whether a rationale exists in combining compounds activating AMPK with compounds targeting the phosphatidylinositol‐3‐kinase (PI3K)/Akt/mTOR/p70S6K signalling pathway. AMPK down‐regulation by specific small‐interfering RNAs confirmed that activated AMPK had a role in restraining growth of GH3 cells. Hence, we compared the effects of compounds directly targeting the mTOR‐p70S6K axis, namely the mTOR inhibitor rapamycin and the p70S6K inhibitor PF‐4708671, with the effects of the AMPK activator 5‐aminoimidazole‐4‐carboxamide ribonucleoside (AICAR) on cell signalling and cell growth, in rat pituitary GH3 cells. AICAR was able to reduce growth factor‐induced p70S6K activity, as shown by the decrease of phospho‐p70S6K levels. However, it was far less effective than rapamycin and PF‐4708671. We observed significant differences between the growth inhibitory effects of the three compounds in GH3 and GH1 cells. Interestingly, PF‐4708671 was devoid of any effect. AICAR was at least as effective as rapamycin and the co‐treatment was more effective than single treatments. AICAR induced apoptosis of GH3 cells, whereas rapamycin caused preferentially a decrease of cell proliferation. Finally, AICAR and rapamycin differed in their actions on growth factor‐induced extracellular signal regulated kinase 1/2 phosphorylation. In conclusion, the results of the present study suggest the increased efficacy of combined antiproliferative therapies, including rapamycin analogues and AMPK activators in GH‐secreting pituitary tumours, as a result of complementary and only partially overlapping mechanisms of action.